Analisis Perbandingan Penerapan Konsep Checks and Balances dalam Proses Legislasi di Amerika Serikat, Rusia, dan Indonesia - Rianda Dirkareshza; Eka NAM Sihombing; Muhammad Fauzan (Jurnal Penelitian Hukum De Jure, 2025)
In the framework of Indonesia's constitutional governance, the principle of checks and balances among constitutional institutions is an essential component of the legal system. Indonesia adopts a bicameral legislative system involving the House of Representatives (Dewan Perwakilan Rakyat; DPR) and the Regional Representative Council (Dewan Perwakilan Daerah; DPD). However, DPD possesses limited legislative authority, particularly in drafting laws. Additionally, judicial oversight is conducted by the Supreme Court (Mahkamah Agung/MA). This issue gives rise to research questions pertaining to  raised in this study are about the oversight concept in the lawmaking process from the perspective of comparative constitutionalism and the reconstruction of the oversight concept to realize enhance checks and balances. This study employs a mixed -method approach, incorporating normative-juridical, comparative, and conceptual methodologies  and legislative analysis. The findings indicate that Indonesia implements a soft bicameral concept characterized by an asymmetry of authority with in between the two both chambers in the lawmaking process, with the Constitutional Court acting as the primary a judicial oversight mechanism. In contrast, the United States and Russia maintain robust internal oversight within their legislative institutions, complemented judicial authority to oversee law implementation, thereby reinforcing  checks and balances between the legislative and judicial branches. It is recommended that the oversight framework within Indonesia's legislative process be strengthened by reconstructing oversight mechanisms through the expansion of the DPD's role, particularly in reviewing, approving, or vetoing draft legislation. This expansion is advised to enhance internal legislative oversight and create a more balanced system of checks and balances between legislative bodies. Furthermore, the reconstruction of oversight concepts in the lawmaking process should be pursued by granting the DPD greater authority to accept or veto draft laws, thereby reinforcing internal oversight within the legislative process